O Porvir, jornal literário e recreativo : propriedade de uma associação de estudantes do Atheneu Sergipense (1874) - Rodrigues, Cibele de Souza (2016)
This thesis has as its main object of study the student newspaper O Porvir, dated from 1874, belonging to the first student organization of Atheneu Sergipense, a secondary institution of education in Sergipe. The research focuses on analyzing the educational topics discussed in the newspaper by a group of students from Atheneu Sergipense, on the twelve editions that were located, from that time. The timeframe is between August and November of 1874, because of the dating of the selection of O Porvir identified at the Public Library Epifânio Dórea in this period. The study brings in its discussion the comprehension of the constitution as a student space which was compressed in a newspaper organized by the students from Atheneu Sergipense in the 19th century. It was adopted as methodological foundations the dialog between the bibliography and documentary references, such as Laws, Regulations, Reports, Records and the number of editions of the newspaper. Thus, this thesis presents itself in the field of History of Education on the New Cultural History approach, by using main concepts, such as school culture by Vinão Frago (1994) and Dominique Julia (2001), material school culture by Felgueiras (2010), and association by Alex de Tocquebile (2004). Therefore, the study allowed me to comprehend more about the student universe, the preference of that group of the school in 1874 through the writings, which were full of moral, religious, and educational teachings, considered by them as a way to achieve “light” and success. It was also possible to notice a respect defended among the ads and poetry about historical festivities, encouraged by the school, that is, a significant contribution of values for the understanding of the school culture of that time.